Common Bacterial Infections in Post-Surgical Patients: A Study in a Tertiary Care Hospital in Bangladesh - Haque, SK. Mozammel; Rahman, Mohammad Ziaur; Das, Chittaranjan; Salim, Mohammad; Zim, Hasant Zaman; Islam, Md. Ashraful; Hossain, Md. Jahangir; Nahar, Sharmin (Journal of Neonatal Surgery, 2025)
Background: Post-surgical bacterial infections represent a major healthcare challenge in tertiary hospitals, particularly in developing countries like Bangladesh. These infections lead to extended hospital stays, increased treatment costs, and higher rates of antimicrobial resistance. There remains a critical need for local data on infection patterns to guide clinical practice and policy decisions. Objective: To investigate the prevalence, causative organisms, and antibiotic resistance profiles of bacterial infections in post-surgical patients. Methods: A prospective cross-sectional study was conducted at Bangabandhu Sheikh Mujib Medical University from January 2022 to December 2024. Using purposive sampling, 385 post-surgical patients showing clinical signs of infection were included. Samples, including wound swabs, blood, and urine, were collected for microbiological culture and antibiotic susceptibility testing. Data analysis was performed using SPSS version 23.0. Results: The study of 385 post-surgical patients revealed that Gram-negative pathogens (68.3%) predominated, with Escherichia coli (32.5%) being most prevalent. High resistance was observed to cephalosporins (65.4%) and fluoroquinolones (58.7%), while carbapenems remained effective (85.8% susceptibility). Significant risk factors included diabetes (OR = 2.45, p = 0.003) and emergency surgery (OR = 1.89, p = 0.012). Superficial incisional infections (45.2%) were most common, with 72.4% cases emerging within 10 postoperative days. Conclusion: This study highlights a critical burden of multidrug-resistant post-surgical infections in Bangladesh, driven by identifiable risk factors and resistance patterns. Immediate interventions focusing on infection prevention, antimicrobial stewardship, and patient risk stratification are urgently needed to improve surgical outcomes